2019
DOI: 10.1055/a-0839-4283
|View full text |Cite
|
Sign up to set email alerts
|

Gründe für den Ausstieg aus dem Arztberuf und Determinanten, eine ärztliche Tätigkeit wiederaufzunehmen: eine qualitative Studie mit ehemaligen Teilnehmern eines Wiedereinstiegsseminars

Abstract: Zusammenfassung Hintergrund In Deutschland existiert ein zunehmender Bedarf an Ärzten. Zeitgleich gibt es viele approbierte Ärzte, die nicht ärztlich tätig sind. Diese wieder für eine ärztliche Tätigkeit zu gewinnen, wäre eine Maßnahme, dem Gesundheitssystem zeitnah Ärzte zuzuführen. Ziele der Studie waren daher die Exploration individueller Gründe für den Berufsausstieg sowie für die Entscheidung, zurück in den ärztlichen Beruf zu kehren. Ferner sollte der Stellenwert einer Teilnahme an einem Wiedereinstiegss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Previous studies in other settings indicated that by promoting a more family-friendly clinical work environment, mental and physical health risks due to professional burnout may decrease whilst career motivation among physicians may increase [ 24 ]. In times of an ageing medical workforce and staff shortages, well-designed work systems may increase the attractiveness of the medical profession for future generations and may help to retain highly-qualified personnel [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in other settings indicated that by promoting a more family-friendly clinical work environment, mental and physical health risks due to professional burnout may decrease whilst career motivation among physicians may increase [ 24 ]. In times of an ageing medical workforce and staff shortages, well-designed work systems may increase the attractiveness of the medical profession for future generations and may help to retain highly-qualified personnel [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%